2018
DOI: 10.1007/s12035-018-1270-y
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism and Cognitive Disorders during Development and Adulthood: Implications in the Central Nervous System

Abstract: Thyroid hormones (THs) play a critical function in fundamental signaling of the body regulating process such as metabolism of glucose and lipids, cell maturation and proliferation, and neurogenesis, to name just a few. THs trigger biological effects both by directly affecting gene expression through the interaction with nuclear receptors (genomic effects) and by activating protein kinases and/or ion channels (short-term effects). For years, a close relationship between the THs hormones and the central nervous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 110 publications
2
37
0
2
Order By: Relevance
“…Moreover, a large cohort study recently showed that both mild hypo‐ and hyperthyroidism in the first trimester of prenatal brain development altered grey/white matter ratios in the progeny, suggesting that lineage specification was altered in embryonic development . Other neurological disorders including attention‐deficit hyperactivity disorder (ADHD), autism spectrum disorder (ASD) and schizophrenia, characterized by abnormal neuronal numbers and networks, are also suspected to have a developmental aetiology of which suboptimal TH levels might be one of the underlying causes . Lastly, a histological analysis of the brain of an MCT8‐deficient foetus showed loss of some neuronal subtypes, and a hypomyelinated state, suggesting similar problems in NSC biology and specification caused by insufficient TH uptake during early development .…”
Section: Evidence For Thyroid Hormone Regulating Embryonic Nsc Physiomentioning
confidence: 99%
“…Moreover, a large cohort study recently showed that both mild hypo‐ and hyperthyroidism in the first trimester of prenatal brain development altered grey/white matter ratios in the progeny, suggesting that lineage specification was altered in embryonic development . Other neurological disorders including attention‐deficit hyperactivity disorder (ADHD), autism spectrum disorder (ASD) and schizophrenia, characterized by abnormal neuronal numbers and networks, are also suspected to have a developmental aetiology of which suboptimal TH levels might be one of the underlying causes . Lastly, a histological analysis of the brain of an MCT8‐deficient foetus showed loss of some neuronal subtypes, and a hypomyelinated state, suggesting similar problems in NSC biology and specification caused by insufficient TH uptake during early development .…”
Section: Evidence For Thyroid Hormone Regulating Embryonic Nsc Physiomentioning
confidence: 99%
“…Alternatively, lithium can exert this disturbance by initiating cellular hypothyroidism (Bolaris, Margarity, & Valcana, ), reducing the birth weight (Harari et al, ), decreasing the energy balance (Brietzke, Stabellini, Grassi‐Oliveira, & Lafer, ), increasing cytokine imbalances (Grignon & Bruguerolle, ) and activating DNA fragmentation in cerebrum of rats (Shao, Young, & Wang, ). In addition, hypothyroidism impairs development of the monoaminergic system (Ahmed, Abdel‐Latif, Mahdi, et al, ; Ibrahim, Tousson, El‐Masry, Arafa, & Akela, ; Tousson, Ibrahim, Arafa, & Akela, ), causing a pathophysiological status (Van Herck et al, ) and neurodevelopmental disorders (Andersen et al, ; Gilbert, Goodman, Gomez, Johnstone, & Ramos, ; O'Shaughnessy et al, ; Salazar, Cisternas, Martinez, & Inestrosa, ; Thompson et al, ). Thus, the potent variations in the monoamine levels might be an adaptive mechanism to achieve homeostasis in the body following the hypothyroid state induced by LiCl.…”
Section: Discussionmentioning
confidence: 99%
“…In a typically developing brain, increased TH levels enhance and decreased TH levels attenuate dendritic arborization in cerebellar Purkinje cells [183,199]. However, maternal dietary exposure to Aroclor 1254 throughout gestation and lactation at doses of 1 or 6 mg/kg/d increased dendritic arborization or had no effect on dendritic arborization in Purkinje cells, respectively, even though both doses significantly decreased serum TH levels in dams and offspring [47,143].…”
Section: Thyroid Hormone-mediated Mechanisms Of Pcb Developmental Neumentioning
confidence: 97%
“…TH influences many stages of neurodevelopment, and congenital hypothyroidism is linked to significant neurodevelopmental defects [180][181][182][183]. There is some evidence, albeit conflicting, that TH insufficiency may increase the risk of ASD [184,185] and is related to ADHD [186,187].…”
Section: Thyroid Hormone-mediated Mechanisms Of Pcb Developmental Neumentioning
confidence: 99%